Determination of Endogenous Peptides with in Vitro ACE Inhibitory Activity in Normotensive Human Plasma by the Fluorometric HPLC Method - Matsui, Toshiro; Matsufuji, Hiroshi; Kawasaki, Terukazu; Osajima, Yutaka (Bioscience, biotechnology, and biochemistry, 1997)
An in vitro degradation test of angiotensin (ANG) II or III in normotensive supine human plasma from 9 healthy male subjects confirmed the production of smaller ANG metabolites with angiotensin I-converting enzyme inhibitory activity. These metabolites were identified as ANG (3-8), ANG (4-8), ANG (5-8), and ANG (3-4), whose respective peptide concentrations were determined by our proposed naphthalene-2, 3-dialdehyde (NDA)-HPLC method to be 64 ±9, 39 ±5, 176 ± 22, and 197 ± 35 fmol/ml of plasma.